Are dyads conditionally cooperative? Evidence from a public goods experiment - Andrea Morone; Tiziana Temerario (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
We analysed dyads strategies in one-shot public goods game. By means of a laboratory experiment, using a variant of the strategy-method, we found that more than one third of the dyads are conditional cooperators, whereas 18% can be categorised as free riders.
Keywords: H41; C91; 330; Voluntary contributions; Conditional cooperation; Free riding; Strategy-method